Correction: Ullah et al. Natural Polyphenols for the Preservation of Meat and Dairy Products. Molecules 2022, 27, 1906 - Hammad Ullah; Yaseen Hussain; Cristina Santarcangelo; Alessandra Baldi; Alessandro Di Minno; Haroon Khan; Jianbo Xiao; Maria Daglia (Molecules)
In the original publication [...]